Polysulfide-triggered fluorescent indicator suitable for super-resolution microscopy and application in imaging. Issue 30 (28th March 2018) - A., Anila Hoskere; Sreedharan, Sreejesh; Ali, Firoj; Smythe, Carl G.; Thomas, Jim A.; Das, Amitava
Abstract : A new physiologically benign and cell membrane permeable BODIPY based molecular probe, MB-S n, specifically senses intracellular hydrogen polysulfides (H2 S n, n > 1) localized in the endoplasmic reticulum. Abstract : A new physiologically benign and cell membrane permeable BODIPY based molecular probe, MB-S n, specifically senses intracellular hydrogen polysulfides (H2 S n, n > 1) localized in the endoplasmic reticulum. This reagent is suitable for mapping the intracellular distribution of H2 S n by wide-field as well as super-resolution Structured Illumination Microscopy (SIM).